Sugar content in Malaysian foods for updating the Malaysian food composition database - Nurul Aznyda Norizan; Norhayati Mustafa Khalid; Rusidah Selamat; Siti Noor Hamizah Adam; Nurdiyana Abd Manap; Khairul Nisa’ Ishak; Tee E Siong; Mohd Fairulnizal Md Noh (Applied Food Research)
Sugar is consumed daily through a wide variety of foods and beverages. The lack of data on sugar content of a wide variety of foods in the current Malaysian Food Composition Database (MyFCD) is an important reason for lack of research on sources of sugar to the daily diet of the community. Hence, the objective of this study is to determine the amount of sugar in the Malaysian foods and beverages which subsequently to update the data in the MyFCD. Approximately 118 foods were selected based on the findings of the Malaysian Adult Nutrition Survey (MANS) 2014. These include pre-packaged foods as well as various local desserts and foods. All the foods were divided into eight categories which are (i) cereal and cereal products; (ii) jam and jelly; (iii) traditional Malaysian kuih and cakes; (iv) beverages; (v) coffee, tea and related products; (vi) milk and milk products; (vii) instant beverages premix high in added sugar; (viii) miscellaneous. The amount of sugar content was determined using High Performance Liquid Chromatography with Refractive Index Detector.This study showed that sucrose is the most common sugar content available in the cereal and cereal products, traditional Malaysian kuih and cakes and variety of beverages. Fructose and glucose were highly available in jam and jelly and lactose was mostly found in milk and milk products. These findings can assist Malaysian in identifying high sugar foods and beverages and making healthier food choices.